She made a monster : how Mary Shelley created Frankenstein - Fulton, Lynn (Alfred A. Knopf, 2018)
On a stormy night two hundred years ago, a young woman sat in a dark house and dreamed of her life as a writer. She longed to follow the path her own mother, Mary Wollstonecraft, had started down, but young Mary Shelley had yet to be inspired. As the night wore on, Mary grew more anxious. The next day was the deadline that her friend, the poet Lord Byron, had set for writing the best ghost story. After much talk of science and the secrets of life, Mary had gone to bed exhausted and frustrated that nothing she could think of was scary enough. But as she drifted off to sleep, she dreamed of a man that was not a man. He was a monster.